Researchers’ self-archiving behavior towards open-access institutional repositories - Prastowo, Rahardito Dio; Saputro, Singgih Dwi; Sensuse, Dana Indra; Lusa, Sofian; Putro, Prasetyo Adi Wibowo; Indriasari, Sofiyanti (Universitas Padjadjaran, 2024)
The success of open-access repositories depends heavily on researchers’ willingness to disseminate their research through self-archiving. Previous studies indicated that lack of self-archiving was a major obstacle to the success of institutional open-access repositories. This study aimed to identify factors influencing researchers' behavior in self-archiving. The analysis examined the influence of repository performance expectations, effort expectations, social influence, and facilitating conditions on researchers' self-archiving intentions and behavior. The study also explored the moderating role of demographic factors such as gender, age, and experience in the relationship between the analyzed factors and self-archiving intentions and behavior. Furthermore, this study also revealed the direct impact of regulatory awareness and research discipline on self-archiving intentions and behavior. The research findings showed that social influence significantly affected researchers' intentions to self-archive while facilitating conditions had a substantial impact on self-archiving behavior. Additionally, demographic variables, such as gender, age, and experience, were found to moderate the effects of social influence on behavioral intention, while awareness of regulations contributed directly to self-archiving behavior. These findings highlight the importance of strengthening social influence, providing adequate supporting conditions, and implementing supportive policies and regulations to enhance researchers' self-archiving behavior in open-access institutional repositories.